Tax Shelter Alternatives: Measuring the Risks (Book). - Wyndelts, Robert W.; Hendrickson, Harvey S. (The Accounting Review, 1986)
Reviews the book "Tax Shelter Alternatives: Measuring the Risks," by Michael N. Fitzgerald.